Analysis ANALYSIS OF STUDENT WORKSHEETS (LKPD) BASED ON PROBLEM BASED LEARNING ON STUDENT LEARNING OUTCOMES: . - Citra Gusyanti; Sujarwo (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
Abstract:. The purpose of this study is to analyze the effective and efficient LKPD as teaching materials to help the teaching and learning process achieve its goals. LKPD can be combined with learning models so that they can be effective and efficient teaching materials and can improve student learning outcomes. One of the learning models that can be used is problem based learning. LKPD-based is one model of LKPD which is centered on increasing the effectiveness of learning. The development of LKPD based on problem based learning for students as a companion for student learning activities is expected to be able to improve the quality of learning, so that student learning outcomes can increase. The method used in this research is a qualitative approach research method. including case studies, biographies, ethnography, and library searches. The subject of the trial was a librarian, who was in the library of the Muslim Nusantara University, Al Washliyah Medan. The object of this research is LKPD in science subjects. The research time is planned for July 2021. The research procedures that must be carried out to produce LKPD teaching materials consist of types of research that are included in research with a qualitative approach including case studies, biographies, ethnography, and library searches. In this study, the type of research that the researcher did was included in the literature research or library (library search). The instrument in this study, the researcher acts as a planner, data collector who then interprets the data that has been collected. In conducting the research, the researcher collects as much data as possible so that the research results are accurate. systematically search and compile data obtained from interviews, field notes, and documentation by organizing data into categories, breaking down into units, synthesizing, compiling into patterns, choosing what is important and what will be studied and making conclusions so that it is easily understood by themselves and others. Analysis means reviewing the data obtained from the field by organizing the data into categories, breaking it down into units, choosing which ones are important and will be studied, Keywords: Problem Based Learning, Student Worksheets, Learning Outcomes